ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA MENTARI SWALAYAN MUARA BUNGO - Rita Friyani; Sri Rahayu; Akbar Alfarisi (Universitas Merdeka Madiun, 2023)
This study aims to find out how the application of cash sales accounting information systems at Mentari Swalayan Muara Bungo. This study used a purposive sampling method with a total sample of 25 people. This type of research is a case study with data collection techniques used, namely interviews, documentation and questionnaires. The data analysis technique used to answer the problem formulation is a descriptive qualitative technique by describing the cash sales accounting information system applied to Mentari Swalayan Muara Bungo. The results of this study indicate that the implementation of the Cash Sales Accounting Information System at Mentari Swalayan Muara Bungo is very good, however there are still some weaknesses such as incomplete accounting records in the form of general journals, sales journals, cash receipts journals and accounting records in the form of warehouse cards.